A review of organic UV-filters in wastewater treatment plants. (January 2016) - Ramos, Sara; Homem, Vera; Alves, Arminda; Santos, Lúcia
Abstract: UV-filters are a group of compounds which have been massively used in the past years due to the recent concerns with sunburns, premature skin ageing and the risk of developing skin cancer, related to sun exposure. At the moment, these compounds have been identified by the scientific community as emerging pollutants, due to their persistence in the environment, potential to accumulate in biota and potential threat as endocrine disruptors. At some point, the majority of sunscreens will find their way into wastewater (due to bathing and washing activities) and because wastewater treatment plants (WWTPs) are not able to remove and/or degrade them, consequently they find their way into rivers, lakes and ocean, so it is not surprising that UV-filters are found in the environment. Therefore, wastewater treatment plants should be the focus of the scientific community aiming to better understand the fate of the UV-filters and develop new technologies to remove them from wastewater and sludge. This review, aims to provide the current state of the art in the occurrence and fate of UV-filters in wastewater treatment plants and how the technologies that are being used are successfully removing these compounds from both wastewater and sludge. Highlights: UV-filters are emerging compounds frequently found in wastewater and sludge. Hydrophilic compounds like BP3 and BP4 tend to accumulate in wastewater up to mg/L. Lipophilic compounds like EHT and OC tend to sorb onto sludge up to μg/g-dw range. Conventional WWTPs are not able for removing UV-filters from water and sludge. Reverse osmosis is the more effective treatment but operational costs are very big.